THE STREAM-OF-CONSCIOUSNESS TECHNIQUE IN NONTRADITIONAL NOVELLAS: NEW STYLISTIC EXPLORATIONS IN UZBEK LITERATURE - Botirova Shaxlo Isamiddinovna (International Scientific and Current Research Conferences, 2025)
This article examines how the stream-of-consciousness technique has been adapted within nontraditional Uzbek novellas (qissa) in the twenty-first century. Building on narratological and stylistic theory, it argues that Uzbek prose deploys interior monologue, free indirect discourse, associative montage, and syntactic loosening to register memory, displacement, and moral ambivalence in a transforming society. Methodologically, the study combines close reading with comparative poetics, relating the Uzbek qissa’s episodic heritage and oral-lyric coloration to modernist and postmodernist protocols inherited from world literature. The results show that stream-of-consciousness in Uzbek novellas is less an import than a localization: it integrates vernacular rhythm, code-switching, and documentary shards (letters, chat logs, prayers) to envoice subjectivities historically under-articulated in print. The technique reconfigures focalization, temporal pacing, and the chronotope of home/journey/return, enabling polychronic narration where present action is braided with recollective and visionary time. The conclusion highlights implications for pedagogy, translation, and future research, positioning the nontraditional Uzbek qissa as a laboratory for ethically attentive, cognitively demanding forms of narration.